2021
DOI: 10.1161/circheartfailure.121.008532
|View full text |Cite
|
Sign up to set email alerts
|

Protein Aggregation Is an Early Manifestation of Phospholamban p.(Arg14del)–Related Cardiomyopathy: Development of PLN-R14del–Related Cardiomyopathy

Abstract: Background: The p.(Arg14del) pathogenic variant (R14del) of the PLN (phospholamban) gene is a prevalent cause of cardiomyopathy with heart failure. The exact underlying pathophysiology is unknown, and a suitable therapy is unavailable. We aim to identify molecular perturbations underlying this cardiomyopathy in a clinically relevant PLN-R14del mouse model. Methods: We investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…To investigate whether administration of a PLN-ASO could halt or even reverse established PLN-R14del cardiomyopathy, we aimed to initiate treatment when PLN-R14 Δ/Δ mice had considerable HF. Based on previously published data on the development of DCM in PLN-R14 Δ/Δ mice [ 15 , 16 ], we decided to start PLN-ASO injections at 5 (ASO-early) or 6 (ASO-late) weeks of age when mice were shown to exhibit moderate (27.5 ± 0.2% fractional shortening (FS) vs. 36.2 ± 1.1% in age-matched wild-type (WT) controls) or severe (13.6 ± 2.3% FS) LV dysfunction with ventricular dilatation, respectively ( Figure 1 A and Figure S1 ). As expected [ 16 ], vehicle-treated PLN-R14 Δ/Δ mice reached a humane endpoint at 8.1 ± 0.5 weeks of age ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To investigate whether administration of a PLN-ASO could halt or even reverse established PLN-R14del cardiomyopathy, we aimed to initiate treatment when PLN-R14 Δ/Δ mice had considerable HF. Based on previously published data on the development of DCM in PLN-R14 Δ/Δ mice [ 15 , 16 ], we decided to start PLN-ASO injections at 5 (ASO-early) or 6 (ASO-late) weeks of age when mice were shown to exhibit moderate (27.5 ± 0.2% fractional shortening (FS) vs. 36.2 ± 1.1% in age-matched wild-type (WT) controls) or severe (13.6 ± 2.3% FS) LV dysfunction with ventricular dilatation, respectively ( Figure 1 A and Figure S1 ). As expected [ 16 ], vehicle-treated PLN-R14 Δ/Δ mice reached a humane endpoint at 8.1 ± 0.5 weeks of age ( Figure 1 B).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that, like in human patients [ 10 , 24 ], intracardiomyocyte aggregation of PLN proteins is an early hallmark of PLN-R14del cardiomyopathy in mice [ 15 ]. To determine PLN protein distribution, we performed immunofluorescent staining for PLN on cardiac sections.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations